Alterations of the human gut microbiome in multiple sclerosis - Jangi, Sushrut; Gandhi, Roopali; Cox, Laura M.; Li, Ning; von Glehn, Felipe; Yan, Raymond; Patel, Bonny; Mazzola, Maria Antonietta; Liu, Shirong; Glanz, Bonnie L.; Cook, Sandra; Tankou, Stephanie; et al. (Nature communications, 2016)
The gut microbiome plays an important role in immune function and has been implicated in several autoimmune disorders. Here we use 16S rRNA sequencing to investigate the gut microbiome in subjects with multiple sclerosis (MS, n =60) and healthy controls ( n =43). Microbiome alterations in MS include increases in Methanobrevibacter and Akkermansia and decreases in Butyricimonas , and correlate with variations in the expression of genes involved in dendritic cell maturation, interferon signalling and NF-kB signalling pathways in circulating T cells and monocytes. Patients on disease-modifying treatment show increased abundances of Prevotella and Sutterella , and decreased Sarcina , compared with untreated patients. MS patients of a second cohort show elevated breath methane compared with controls, consistent with our observation of increased gut Methanobrevibacter in MS in the first cohort. Further study is required to assess whether the observed alterations in the gut microbiome play a role in, or are a consequence of, MS pathogenesis. The gut microbiome has been implicated in several autoimmune disorders. Here, the authors study the gut microbiome of patients with multiple sclerosis, and find correlations between altered abundance of certain gut microorganisms and changes in expression of immune defence genes.